The Evaluation of Users’ Acceptance of a Computer-based HIS at Benghazi Diabetes Centre - Awami, Salah (Journal of Health Informatics in Africa, 2024)
Background and Purpose: This study investigated whether an electronic medical record implemented at a medical centre was successful and shed the light on some of the factors that may have contributed to such outcome. Important indicators of the system’s success include its acceptance by the users, meaningful use, and likelihood of sustainability. The users’ acceptance is a reflection of their satisfaction with the amount of effort required, the amount of benefits realized, and the kind of experience they’ve developed using the system. Methods: based on user acceptance literature, a questionnaire was designed and administered to clinicians at the medical centre. 18 clinicians participated in this qualitative, descriptive, cross-sectional study to evaluate users’ acceptance of the system. Results: expressing general impression, 56% of the participants think that the system is easy to use and 61% judge the system as useful for supporting their work tasks. Regarding their use experience, third of the participants object that the system’s performance was timely and more than 80% agree that the system facilitates data documentation and medication order. Conclusions: despite the system’s suboptimal performance, it is accepted by the users and it is well integrated into their routine work. The few participants who evaluate the system negatively may belong to ‘late adopters’ group who will eventually adopt. Users’ self-efficacy, the mandatory policy of the centre and the leadership of the centre management are some of the factors that may have contributed to such outcome. Issues of system performance and some of the participants’ requirements ought to be addressed to insure the system’s sustainability.